Analysing material flows of landfill mining in a regional context. (10th January 2019) - Hölzle, Ingo
Abstract: Landfill mining (LFM) is considered an option to recover recyclables and at the same time to prevent environmental hazards as well as an option to reclaim land. With regard to the environmental sustainability of LFM, previous research has focused on life-cycle assessment and the climate impact of energy generation using refuse-derived fuel from mined landfills. These studies were commonly based on hypothetical models paying little attention to emissions resulting from operations (e.g. excavation, processing, transportation). Since LFM involves a broad range of stakeholders, the objective of the present study is to investigate LFM empirically in a regional context using data from eight mined landfills in Germany. A material flow analysis, which included a calculation of energy consumption and related emissions from operations, was carried out and factors affecting material flows were determined based on environmental scanning. LFM operations required on average 103 MJ diesel (≙2.4 kg) and 1.9 MJ electricity per tonne excavated waste, producing 12 kg of CO2 equivalent. Transportation proved to be the sub-process with the largest energy consumption by far, producing 58% of total emissions, followed by processing (27%). The average transportation distance was 122 km; however - in contrast to previous studies - transportation distances for recovered soils (84 km) and asphalt (175 km) were considerably longer. Decisive for energy consumption were: a) the option of excavating waste lifts one at a time, b) an on-site processing option, c) processability of waste, and d) an on-site reuse option and/or nearby recovery facilities for soils. Flexibility, pragmatism and coordination of stakeholders proved to be key factors due to the complex and individual character of LFM projects as well as numerous interfaces. Graphical abstract: Image 1 Highlights: Analysis of regional material flows for eight mined landfills. Calculation of energy consumption and carbon footprint for landfill mining operations. Comprehensive analysis of factors influencing landfill mining in practice. Emphasis on logistics of soils.